Workplace factors and care seeking for low-back pain among female nursing personnel - Josephson, Malin; Vingård, Eva; MUSIC-Norrtälje Study, Group (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVES ': 'Low-back pain is common among nursing personnel, and its origin is multifactorial. The present study focused on physical and psychosocial work load. The objectives of the study were to estimate the relative risk for nursing personnel, compared with other occupational groups, to seek health care for low-back pain, and to identify risk factors.' ' METHODS ': 'This study is a part of a population-based case-referent study in the municipality of Norrtälje, situated north of Stockholm. Altogether 333 women served as cases and 733 served as referents. Eighty-one cases and 188 referents were employed in nursing work. The cases had sought health care for low-back pain during the study period, November 1993 to November 1996. The referents were randomly selected from the same population. The subjects filled out 2 questionnaires and participated in interviews about physical exposures and psychosocial factors.' ' RESULTS ': 'When the female nursing personnel were compared with other employed women, no increased risk of consultation for low-back pain was found. According to a multivariate logistic regression, nursing personnel exposed to forward-bending working positions, high energetic work load, perceived physical exertion, or insufficient social support had the highest risk estimates. In univariate analyses, the combination of physical and psychosocial risk factors was associated with a particularly high risk.' ' CONCLUSION ': 'In nursing work, physical load seems to be more significant than psychosocial factors when a worker seeks health care for low-back pain. The results of did not support the hypothesis that nursing work is a risk occupation for seeking care for low-back pain when compared with other occupations.
Keywords: case-referent study; epidemiology; female; health care; low-back pain; nursing personnel; physical load; psychosocial factor; woman; workplace